The effect of religiosity and tacit self-declare halal cues on skepticism and patronage intention of self-declare halal restaurant - Catur Sugiarto; Reza Afrizal (Jurnal Manajemen dan Pemasaran Jasa, 2023)
The food industry is significantly prominent for exhibiting consumer segmentation in countries developing their halal industry. Due to the absence of appropriate certification, not all businesses within the industry employ authentic labels, leading to self-declare claims as a means of assuring consumers of the halal status of their products or services. Therefore, this study aimed to contribute to the advancement of marketing communication literature, by specifically enhance skepticism the impact of religiosity (REL), as well as implicit self-declare halal cues on (SKEP) and patronage intention (PIE) among relevant restaurant consumers. To obtain significant information, an online questionnaire was implemented and distributed to 297 participants. The results showed that both REL and tacit self-declare halal cues (TSHC) negatively affected SKEP towards relevant restaurants. From this context, more TSHC shown in the restaurant and the higher level of REL led to less SKEP of consumers. Mediation analyses were also implemented to evaluate the indirect relationship between these variables. This emphasized the construction of a mediation model to provide subsequent insights into the mediating role of SKEP and its attitude towards halal restaurants (ATHR). Based on the results, SKEP played a mediating role in the relationships between REL-PIE and TSHC-PIE.